A Preliminary Study of the Lacquerware of the Northern Dynasties, with a Special Focus on the Pingcheng Period (398–493). (1st January 2019) - Müller, Shing
Abstract : After the Han, lacquer finds in tombs in the Chinese world generally became rare both in the north and in the south. However, in northern China, especially during the Pingcheng period (398–493) of the Northern Wei, a certain resurgence was experienced. The later Northern Dynasties then see a drastic reduction in realia finds again. The lacquers in Pingcheng tombs were mostly used to present funerary offerings of sacrificed animals. Many lacquers were presumably products of previous ages, but some were newly manufactured in Pingcheng. In the Pingcheng funerary cult, lacquers were used in novel ways, and with novel ornamentation, as tableware for sacrifices took root in northern Shanxi. Such practices are not found elsewhere. The unique lacquer-painted coffins of Pingcheng bear images of Xianbei or Central Asians, accompanied mostly with motifs and patterns in the style of Yungang art. Based on a dominant human imagery accompanied by decorative elements, the possible origin of the famous lacquered screen from the tomb of Sima Jinlong is also briefly discussed.